2009
DOI: 10.1002/app.29927
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the influence of molecular weight and isotacticity of polypropylene on the formation of mesomorphic phase

Abstract: Polypropylene (PP) blends with various molecular weight and isotacticity were prepared through solution blending and subjected to rapid melt quenching. Structural changes in the PP matrix during mesomorphic phase formation were measured by FTIR spectroscopy and wide-angle X-ray diffraction measurements. The blends with different molecular weight and isotacticity provided the pathway to understand their influence on mesomorphic phase formation. It is observed that low molecular weight PP with low isotacticity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The line located at 830 cm −1 , reported in thin films of iPP deposited from solution,5–8 was observed in this work at 840 ± 2 cm −1 in the thick films of iPP and iPP–VGGCNFs obtained by extrusion. The shift of the position of this line toward higher wavelengths may have originated from differences in the average molecular masses of these samples, different histories (solution vs solid processing), and the highest concentration of chain entanglements in films obtain by extrusion compared to the case of thin films obtained from solution.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The line located at 830 cm −1 , reported in thin films of iPP deposited from solution,5–8 was observed in this work at 840 ± 2 cm −1 in the thick films of iPP and iPP–VGGCNFs obtained by extrusion. The shift of the position of this line toward higher wavelengths may have originated from differences in the average molecular masses of these samples, different histories (solution vs solid processing), and the highest concentration of chain entanglements in films obtain by extrusion compared to the case of thin films obtained from solution.…”
Section: Resultssupporting
confidence: 71%
“…For iPP, regularity bands are located below 1400 cm −1 and are connected to different values of the number n , which describes the minimum number of monomers linked in an isotactic sequence that defines a helical structure. The FTIR lines of iPP located at about 810, 841, 900, 940, 998, 1044, 1103, 1303, and 1330 cm −1 were identified as originating from helical structures, increasing as the temperature is lowered below the melting temperature 5–8. The so‐called regularity bands associated with the helical structures are responsible for the further development of crystallites located at 973, 998, 841, and 1220 cm −1 and have been assigned to chains of isotactic sequences containing 5, 10, 12, and 14 monomer units, respectively 5, 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the average particle size of SBR particles is approximately 20 mesh. According to some relevant studies [20][21][22], PP was calculated and revealed to exhibit isotactic configuration, with a molecular weight of 40,000 g/mol; this constitutes over 95% of the entire polymer content. Polypropylene is recycled PP particles, produced by Hunan Yinghong New Materials Co., Ltd. in Loudi, Hunan Province, China.…”
Section: Materials and Laboratory Test 21 Materialsmentioning
confidence: 99%
“…(The latter is designed to deal with estimation problems that combine linear, mi, and non‐linear, τi, parameters.) Singh et al [ 114 ] proposed a real‐coded genetic algorithm to deconvolute MWDs, attempting to move from local minima to the global minimum. Recently, Patil et al [ 115 ] proposed a numerical method—jitter differential evolution—to deconvolute MWDs that they claim offers some advantages over the previous deconvolution algorithms.…”
Section: Looking Back At the Literaturementioning
confidence: 99%